2013
DOI: 10.1002/ppsc.201300302
|View full text |Cite
|
Sign up to set email alerts
|

Production of 18F‐Labeled Titanium Dioxide Nanoparticles by Proton Irradiation for Biodistribution and Biological Fate Studies in Rats

Abstract: A simple and straightforward method is presented for the direct proton beam activation of 18O‐enriched titanium dioxide nanoparticles (TiO2 NPs) via the 18O(p,n)18F nuclear reaction in order to assess the biological fate of the NPs using positron emission tomography (PET). The radiolabeling of the NPs does not alter their morphological properties as demonstrated by transmission electron microscopy and dynamic light scattering measurements. The simultaneous formation of other radioisotopes by activation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Additionally, post-irradiation TEM images were not taken to test the integrity of Zn@Au NPs after proton bombardment. However, Pérez-Campaña et al 49 showed that proton bombarded TiO 2 NPs were stable and the changes in the size distribution of proton-bombarded TiO 2 NPs were minimal (i.e., before/after bombardment 7.8±2.6/7.4±2.9 nm) for similar measurement conditions (target current@5 µA, irradiation time@6 min). Additionally, although photon and electron emissions from radioactive Zn@Au NPs were characterized by MC simulations in this study, effective dose (or risk) due to the presence of radioactive Zn@Au NPs in human body and organs were not addressed either analytically or using MC simulation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, post-irradiation TEM images were not taken to test the integrity of Zn@Au NPs after proton bombardment. However, Pérez-Campaña et al 49 showed that proton bombarded TiO 2 NPs were stable and the changes in the size distribution of proton-bombarded TiO 2 NPs were minimal (i.e., before/after bombardment 7.8±2.6/7.4±2.9 nm) for similar measurement conditions (target current@5 µA, irradiation time@6 min). Additionally, although photon and electron emissions from radioactive Zn@Au NPs were characterized by MC simulations in this study, effective dose (or risk) due to the presence of radioactive Zn@Au NPs in human body and organs were not addressed either analytically or using MC simulation.…”
Section: Discussionmentioning
confidence: 97%
“…When injected into mice, TiO 2 NPs showed an excellent time-dependent biodistribution; however, owing to the relatively short decay half-life of 18 F (109 min), in vivo imaging was obtainable only up to 8 h after injection. 49 In addition,TiO 2 NPs are likely less effective than GNPs for radiosensitization, due to relatively smaller atomic numbers of TiO 2 (23 for titanium and 6 for oxygen, compared with 79 for gold).…”
Section: Introductionmentioning
confidence: 99%
“…One possibility to overcome this problem consists of labeling the metal oxide NPs with radionuclides that can lead to their detection in biological systems by means of ultrahigh sensitivity techniques such PET or SPECT as is routinely done for pharmaceutical compounds. 140,141 For example, Pérez-Campaña and coworkers 141 reported the production of 18 F-labeled TiO 2 NPs by proton irradiation for biodistribution and biological fate studies in rats. The accumulation of NPs in different organs was quantified during almost 8 h after administration.…”
Section: D Nanocarriersmentioning
confidence: 99%
“…Recently, the production of [ 18 F]TiO 2 via proton irradiation of 18 O-enriched TiO 2 -NPs was described by Pérez-Campaña et al (2014). This radiolabeling option is very suitable for short-term experiments (e.g., diagnostic applications using imaging techniques such as positron emission tomography (PET) and living organisms e.g., rats) but not reasonable for long-term experiments due to the half-life of 18 F (t 1/2 * 1.8 h).…”
Section: Introductionmentioning
confidence: 99%